Model Aplikasi Structural Equation Modelling (SEM) Untuk Kebijakan Profesionalisme Perwira TNI Angkatan Laut - Nugroho, Sukmo Hadi; Suharyo, Okol Sri; Chrys, Aang (Universitas Trunojoyo Madura, 2022)
The development of the Indonesian Navy's strength is carried out through a strategic planning process manifested in four activity programs, namely (1) the Marine Readiness Support Program; (2) Modernization Program for Alutsista and Non-Alutsista as well as the Development of Facilities and Infrastructure for the National Defense for Marine; (3) Professionalism Enhancement Program for Marine Personnel; (4) Marine Management and Operation Implementation Program. The Indonesian Navy realizes that the main strength of all force-building programs lies in the quality of the human resources (HR) possessed by the Indonesian Navy. However, the existing reality reveals various kinds of problems and obstacles that hinder the process of improving the quality of existing human resources. For this reason, the Indonesian Navy seeks to improve the pattern of training for personnel by issuing policies that spur the performance of the personnel development system within the Indonesian Navy. From these problems, a research or modeling is needed that can represent how the influence of the Indonesian Naval Personnel Development Pattern and Indonesian Navy Policy on Officer Professionalism to create superior navy personnel in line with the Indonesian Navy development program towards the World Maritime Axis. The method used in this research is Structural Equation Modeling (SEM). There are 27 indicators consisting of 5 indicators of Angkatan Laut policy variables, 13 indicators of personnel development variables and 9 indicators of professionalism. The results showed that there was a significant direct influence between the Angkatan Laut policy variables on personnel development, personnel development on professionalism and Angkatan Laut policies on professionalism. In addition, there is an indirect influence between Angkatan Laut policies on professionalism through personnel development as a mediating variable.